Improvement of Student Reasoning Skills through the Development Model of Advance Organizer on Open Ended Approach - Sulianto, Joko; Sunardi; Anitah, Sri; Gunarhadi; Perdana, Ryzal (International Journal of Psychosocial Rehabilitation, 2020)
Improving students’ reasoning skills can be gained by improving the quality of learning oriented to higher-order thinking skills. Development of learning models is very necessary to improve students’ reasoning skills. The purpose of this study is to produce a learning model that can enhance students’ reasoning skills in mathematics in elementary school. The research approach used in development research consists of a preliminary stage, a development phase and a testing phase. Based on the analysis of research, it is inferred that: (1) It is necessary to develop a learning model oriented to students’ reasoning skills in elementary schools, namely an advanced organizer model based on an open-ended approach, (2) the resulting development model meets the content validity with valid criteria, and validity constructs with very valid criteria, practicality of the advanced organizer model with very valid criteria, (3) an advanced organizer model based on an open-ended approach is effective for improving elementary school students skills on reasoning. The development is carried out to improve the reasoning skills as they are important in learning mathematics.